The Role of Cognitive Empathy on Adolescents’ Phubbing During Pandemic Covid-19 - Rizkyanti, Charyna Ayu; Edyta, Nabilah; Fitrusti, Nefira Dewi (Universitas Islam Negeri Raden Intan Lampung, 2021)
During the Covid-19 pandemic, various activities, including the learning process, have shifted to digital platforms. This is a serious concern because teenagers interact more easily with smartphones than pay attention to other people during social interactions, which is called